(untitled) (Research, Society and Development, 2022)
Despite the remarkable gains in performance research, public administration field still lacks more empirical analysis of the organizational capacity-government performance relationship and objective measures of organizational capacity. We shed light on the role how capacity enhances performance. By using secondary longitudinal data, we focus on the actions taken by 5,570 Brazilian municipalities to prevent or reduce damage caused by natural disasters. Droughts represent a significant impact on the environment of the region, affect local economy and bring misery to the population. Our hypotheses investigate whether mayors’ competence and/or municipal capabilities influence the governmental response to prevent or reduce damage caused by natural disasters. Results provide support for all three hypotheses meaning that when considering both internal dimensions of capacity, it is possible to predict the probability of a municipality adopts actions pro-environment to prevent or reduce damage caused by droughts. Although government faces various constraints, we contribute to investigate subnational organizational capacity as an input to performance of municipalities giving research a more fulsome assessment of government quality.